Outcome of Abdominal Tuberculosis Complicated by Portal Hypertension, Pulmonary Tuberculosis, and Severe Acute Malnutrition - Pattinasarany, Liona Christy; Widowati, Titis; Setyati, Amalia (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Abdominal tuberculosis (TB) is a form of extrapulmonary TB that can present with or without involvement of the lungs. The diagnosis is difficult to establish, which may lead to diagnostic delays. Effective management of adolescent TB requires a holistic approach from various medical disciplines and interventions. This case presented a rare case 13-year-old girl diagnosed with abdominal TB Case: A 13-year-old girl presented with seven-months history of subfebrile fever, lymph node enlargement, abdominal distention, pallor, and severe weight loss. She was diagnosed with abdominal TB. The diagnosis was further complicated by portal hypertension, pulmonary TB, and severe acute malnutrition. To address these challenges, a multidisciplinary treatment plan was implemented and closely monitored for a period of 12 months Discussion: Multiple factors are significantly contributing to the successful outcome of the treatment for abdominal tuberculosis, including good adherence to the prescribed anti-tuberculous medications, absence of side effects from the drugs, the patient's positive knowledge, attitude and health behaviours, and housing and environmental health. Conclusion: This case highlights the importance of factors influencing disease outcomes of abdominal TB. Proper management of the factors would lead to significant clinical and nutritional status improvement, reduce TB transmission, and improved the overall quality of life.